Evaluation of clinical outcomes of patients with mild symptoms of coronavirus disease 2019 (COVID-19) discharged from the emergency department. - Hamidreza Morteza Bagi (Public Library of Science (PLoS), 2021)
Introduction This study was performed to determine the clinical outcomes of patients with mild symptoms of COVID-19 discharged from the emergency department. Methods The present descriptive-analytical cross-sectional study was performed on 400 patients discharged with a diagnosis of COVID-19 from the emergency departments of hospitals affiliated to Tabriz University of Medical Sciences in the time period of 21 March-21 June, 2020. The disease characteristics and demographic data were collected by phone calls during the first, third, and fourth weeks using a researcher-made questionnaire. Finally, the data were analyzed by univariate logistic regression and cross-tabulation using the IBM SPSS Statistics for Windows, version 20. Results In the first week of follow-up, 23(5.8%) patients died, of whom seven patients were female and 16 were male (mean age of death: 70.73±3.27). Out of 41 (10.3%) patients with underlying diseases, 7 (17.1%) died; but out of 359 (89.8%) cases with no history of disease only 16 (4.5%) died. The risk of death in subjects with a history of underlying diseases was 3.27 times higher than those without a history of disease (P = 0.02) (OR = 3.27, 95% CI, 1.20-8.87); and this risk was 1.41 times higher in patients with more family members (P = 0.04) (OR = 1.41, 95% CI, 1.01-1.97). Furthermore, 81 (20.3%) patients had spread the virus to others in their households and disregarded hygiene guidelines such as washing hands, keeping social distancing, and wearing face masks after discharge. In addition, family members of these patients were 16.37 times more likely to be infected than patients who followed the protocols (P ≤ 0.001) (OR = 16.37, 95% CI, 9.10-29.45). Conclusion Since our findings showed that mortality rate is high in the first week after patients' referral to the emergency departments, the health status of infected people should be carefully monitored daily in this period.